تقييم الأداء المالي للمصارف الإسلامية المطبقة لمعايير المحاسبة الإسلامية(دراسة تطبيقية على مجموعة من المصارف الإسلامية للفترة 2013-2017)). - ملياني, حكيم; شالور, وسام (Université de M'Sila, 2019)
بما أن تقييم الأداء المالي يعتبر من الضمانات الأساسية لنمو واستمرار المصارف عامة والإسلامية خاصة، لذلك قمنا بدراسة تطبيقية على القوائم المالية للمصارف الإسلامية محل الدراسة، باعتبارها تعد مدخلات لعملية التحليل المالي. وقد حاولنا إجراء تقييم للأداء المالي لتلك المصارف الإسلامية من خلال مجموعة من المؤشرات والنسب المالية، وتحليلها وترتيبها وبيان قدرتها على تحقيق أهدافها، واختيار المصرف الأحسن أداء. Since the assessment of financial performance is one of the basic guarantees for the growth and continuity of banks in general and Islamic banks in particular, therefore, we have conducted an applied study on the financial statements of the Islamic banks under study, as an input to the financial analysis process. We have tried to conduct an assessment of the financial performance of these Islamic banks through a combination of indicators and financial ratios, analyzing and arranging them and demonstrating their ability to achieve their objectives, and selecting the best performing bank. L’évaluation de la performance financière étant l’une des garanties fondamentales de la croissance et de la continuité des banques en général et islamiques en particulier, nous avons donc mené une étude appliquée sur les états financiers des banques islamiques étudiées. , qui sont considérés comme des intrants dans le processus d'analyse financière. Nous avons tenté d'évaluer la performance financière de ces banques islamiques à l'aide d'un ensemble d'indicateurs et de ratios financiers, de les analyser et de les organiser, de montrer leur capacité à atteindre leurs objectifs et de choisir la banque la plus performante.
Keywords: Banques islamiques ; évaluation de la performance financière ; ratios financiers ; Islamic Banks ; Financial Performance Assessment ; Financial Ratios ; المصارف الإسلامية ; تقييم الأداء المالي ; النسب المالية